Staphylococcus aureus in food and nares of food handlers in Kuala Pilah, Malaysia - Abdul Mutalib, Noor Azira; Abdul-Rashid, Mohammad-Faid; Mustafa, Shuhaimi; Amin Nordin, Syafinaz; Hamat, Rukman Awang; Osman, Malina (Universiti Putra Malaysia Press, 2012)
The outbreak of food poisoning due to Staphylococcus aureus has been reported with a significant level of morbidity worldwide. In this study, 128 samples taken from nasal swabs of 64 food handlers and 64 food items were collected and analyzed for the presence of S. aureus. The antibiotic susceptibility profiles of the isolates were also determined. Cross-sectional was used as a study design in this research. The isolates were identified as S. aureus based on colonial morphology, gram stain, mannitol salt agar fermentation, catalase and coagulase test. Fifteen (23.4%) of food handlers were positive for S. aureus nasal carriage and 24 (37.5%) of food items were contaminated with an average of 8.4 x 106 CFU/g of S. aureus. All isolates were susceptible to oxacillin and mupirocin respectively. However, 74.4% and 5.1% isolates were resistant to penicillin and erythromycin. Our findings suggest that the prevalence of S. aureus carriage is high among our food handlers and food items. Thus, we believed that there is a need for proper training on food safety among food handlers and quality improvement in the food premises.